Reasonable Treatment Range of Karst Cave Encountered by Super-Large Diameter Shield Tunnel in Strongly Karst-Developed Area - Jiang Wang; Jinwen Yang; Xianglin Yan (Advances in Civil Engineering)
When a super-large diameter shield tunnel passes through a strongly karst-developed area, in order to ensure the stability of the tunnel and economy of karst reinforcement, the reasonable treatment range for a huge number of karst caves needs to be researched. Based on a karst treatment project of a shield tunnel with a diameter of 14.5 m, this paper studies the influence of intrusive fully filled karst caves on the stability of the lining and excavation face by using theoretical calculation. In addition, the safe distance between the tunnel and karst caves outside the tunnel is proposed through numerical simulation, and the corresponding treatment range is obtained. The results show that the bearing capacity of the lining has a certain reserve when the intrusive cave is smaller than a certain size, and the caves filled with plastic or hard plastic clay have sufficient antifracturing ability. Therefore, some small fully filled caves inside the tunnel profile can be left unreinforced. On the other side, the critical safe distance is only 1–2 m for the caves with a size of 3 m, so the outside caves with a size less than 3 m can be left unreinforced in the treatment range farther away from the tunnel. The proposed treatment range is close to similar projects that have been built, indicating that analysis results are reasonable.